SHIFT WORK SLEEP DISORDER - House, Dara (Acta Scientiae et Intellectus, 2024)
Shift work is associated with sleepiness and sleep disorders. Circadian rhythms are vital to sleep and health. Disruption in the circadian rhythms cause shift work sleep disorder. Many studies have been published to examine the impact of shift work sleep disorder on health and wellbeing. This paper is a literature review of shift work sleep disorder, associated health risks, and pharmacological and non-pharmacological interventions.